2021
DOI: 10.1371/journal.pone.0246289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gestational low-protein intake on embryonic kidney microRNA expression and in nephron progenitor cells of the male fetus

Abstract: Background Here, we have demonstrated that gestational low-protein (LP) intake offspring present lower birth weight, reduced nephron numbers, renal salt excretion, arterial hypertension, and renal failure development compared to regular protein (NP) intake rats in adulthood. We evaluated the expression of various miRNAs and predicted target genes in the kidney in gestational 17-days LP (DG-17) fetal metanephros to identify molecular pathways involved in the proliferation and differentiation of renal embryonic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 76 publications
4
44
0
2
Order By: Relevance
“…During kidney development in LP 17GD offspring, we have demonstrated that miR-181c enhanced the expression of Six2 and negatively regulates cell proliferation (Sene et al, 2021), confirming results by Lv et al (2014).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…During kidney development in LP 17GD offspring, we have demonstrated that miR-181c enhanced the expression of Six2 and negatively regulates cell proliferation (Sene et al, 2021), confirming results by Lv et al (2014).…”
Section: Discussionsupporting
confidence: 79%
“…At 21GD, PCNA and c-myc mRNA expression was downregulated (Figure 4) in maternal protein-restricted offspring. Using results obtained in the 17GD metanephros using the same model presented here (Sene et al, 2021) and 21GD and 7DL kidneys, we have traced curves where we can observe the more detailed and comparative view of mRNAs expression control by microRNAs (Figure 4).…”
Section: Mirna Targets and Zeb1/2 Expressionmentioning
confidence: 99%
See 3 more Smart Citations